Improvement of the sustainable performance in a textile company using the lean-green methodology - Alessandra De-La-Flor; Marianella Vigil; Marcos Fernando Ruiz-Ruiz (International Journal of Production Management and Engineering)
The textile industry represents one of the greatest threats to the environment. It is the second most polluting industry, generating hazards with its solid waste, gas emissions, water pollution, among others. The objective of this research was to assess the effects of the implementation of the Lean Green methodology within the textile industry to optimize the sustainable performance of the companies and to address the problems of the sector mentioned above. The case study selected was the dyeing area of a Peruvian textile company where the Lean Green methodology was implemented in a sequential design of six phases to then evaluate its effects on sustainable performance. The findings show that the implementation of the proposed model improves water consumption by 18% and electricity consumption by 43%, which has a positive economic impact. Not only in the environmental area, there is also a 120% increase in productivity. The value of this proposal lies in the fact that it can be replicated in other companies in the sector, both locally and regionally. It was also proposed to include the operational criterion in the measurement of sustainable performance for a better dimensioning of the improvement.